MODELING OF FISH SEIZURES AFTER THE IMPLEMENTATION OF THE CLOSED FISHING SEASON LAW IN THE AMAZON BASIN - Rafael Luis da SILVA; Carlos Edwar de Carvalho FREITAS; Sandrelly Oliveira INOMATA; Lucirene Aguiar de SOUZA; Raniere Garcez Costa SOUSA (Boletim do Instituto de Pesca)
The organization of fisheries in the Amazon region is an important theme, since the current management model is based mainly on the closed fishing season policy. This strategy suspends the catching of specific fish stocks and provides subsidies to professional fishers. Thus, the present study analyzed, through mathematical modeling, the behavioral interfaces of illegal fisheries that occurred between 1992 to 2017 in the Amazon basin, considering the hydrological seasonality and the effect of the presence or absence of the Closed Fishing Season law (CFSL). The data were tabulated and used for the construction of two illegal fishing scenarios. The first showed negative impacts with the absence of the CFSL, indicated by the high number of seizures of illegal catches that occurred during the period in which river water level is rising and showed continued growth over time. However, the second scenario showed apprehension apexes occurring at the beginning of the high-water level and at beginning of the low water level, with a continuous decrease in the seizures of illegal catches due to the new law. Thus, the ecosystem model constructed is a promising instrument for testing hypotheses and for formulating and monitoring management scenarios for fisheries in the region.